Antibacterial efficacy of novel bismuth-silver nanoparticles synthesis on Staphylococcus aureus and Escherichia coli infection models - Castro-Valenzuela, Beatriz Elena; Franco-Molina, Moisés Armides; Zárate-Triviño, Diana Ginette; Villarreal-Treviño, Licet; Kawas, Jorge R.; García-Coronado, Paola Leonor; Sobrevilla-Hernández, Gustavo; Rodríguez-Padilla, Cristina (Frontiers in Microbiology, 2024)
Introduction The emergence of multi-drug-resistant bacteria is one of the main concerns in the health sector worldwide. The conventional strategies for treatment and prophylaxis against microbial infections include the use of antibiotics. However, these drugs are failing due to the increasing antimicrobial resistance. The unavailability of effective antibiotics highlights the need to discover effective alternatives to combat bacterial infections. One option is the use of metallic nanoparticles, which are toxic to some microorganisms due to their nanometric size. Methods In this study we (1) synthesize and characterize bismuth and silver nanoparticles, (2) evaluate the antibacterial activity of NPs against Staphylococcus aureus and Escherichia coli in several infection models (in vivo models: infected wound and sepsis and in vitro model: mastitis), and we (3) determine the cytotoxic effect on several cell lines representative of the skin tissue. Results and discussion We obtained bimetallic nanoparticles of bismuth and silver in a stable aqueous solution from a single reaction by chemical synthesis. These nanoparticles show antibacterial activity on S. aureus and E. coli in vitro without cytotoxic effects on fibroblast, endothelial vascular, and mammary epithelium cell lines. In an infected-wound mice model, antibacterial effect was observed, without effect on in vitro mastitis and sepsis models.